2022
DOI: 10.1186/s12934-022-01917-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for efficient production of recombinant proteins in Escherichia coli: alleviating the host burden and enhancing protein activity

Abstract: Escherichia coli, one of the most efficient expression hosts for recombinant proteins (RPs), is widely used in chemical, medical, food and other industries. However, conventional expression strains are unable to effectively express proteins with complex structures or toxicity. The key to solving this problem is to alleviate the host burden associated with protein overproduction and to enhance the ability to accurately fold and modify RPs at high expression levels. Here, we summarize the recently developed opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 151 publications
0
14
0
Order By: Relevance
“…In this work, an increase in the IPTG concentration did not have an improved effect on enzyme expression, suggesting that 0.1 mM IPTG is a suitable concentration to induce expression. A possible explanation for this fact may include toxicity, saturation of the lac operon, or cell stress response promoted by high concentrations of IPTG, as previously reported (Dvorak et al 2015 ; Gomes et al 2020 ; Zhang et al 2022 ).…”
Section: Discussionmentioning
confidence: 67%
“…In this work, an increase in the IPTG concentration did not have an improved effect on enzyme expression, suggesting that 0.1 mM IPTG is a suitable concentration to induce expression. A possible explanation for this fact may include toxicity, saturation of the lac operon, or cell stress response promoted by high concentrations of IPTG, as previously reported (Dvorak et al 2015 ; Gomes et al 2020 ; Zhang et al 2022 ).…”
Section: Discussionmentioning
confidence: 67%
“…However, nanobodies expressed in the cytosol of E. coli face several problems including the formation of insoluble inclusion bodies, and the inability to form disulfide bonds correctly (17) . Both will ultimately lead to toxicity to the host cell (18) . As data from our lab showed several proteins could be secreted into the culture medium by fusing it with the pelB signal peptide (Figure S1 HdeA, Spy, Im7 secretion).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that this imbalance can be controlled by regulating heterologous gene expression by considering the copy number of a plasmid and the adjusting promoter strength (Lozano Terol et al 2021 ). pET-based expression plasmids were widely used for research and commercial production (Zhang et al 2022 ). This plasmid has a T7 promoter that drives the heterologous expression of recombinant proteins.…”
Section: Essential Components Of E Coli -Based Exp...mentioning
confidence: 99%
“…Several reasons such as lacking post-translational modifications (PTMs), misfolding, lower solubility capacity, and host metabolic burden are involved in creating IBs (Zhang et al 2022 ). One of the strategies to overcome the creation of IBs during the over-expression of recombinant proteins is the co-expression of the target proteins with the chaperone molecules.…”
Section: Molecular Chaperonesmentioning
confidence: 99%